2015
DOI: 10.1007/s13369-015-1708-8
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive FEM with Domain Decomposition Method for Partitioned-Based Fluid–Structure Interaction

Abstract: A numerical assessment on the solution performance of adaptive finite element methods for fluid-structure interaction (FSI) is presented in this paper. The partitionedbased approach involving separate fluid and structure solvers is considered for adaptive finite element computation with triangular mesh. The performance of the hp-adaptivity, in which error in energy norm is reduced by way of mesh refinement (h) and polynomial order extension ( p), is of particular interest. In addition, parallel solution proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
(42 reference statements)
1
2
0
Order By: Relevance
“…Therefore, it is not worth to add more cores at some point when the computation time became saturated. This is consistent with the findings by Abas and Abdul-Rahman in which it was found that as the number of cores increases for similar applied problem, at some point it will reach saturation point where most of the computation time is spent on the interconnection and communication between individual cores [ 75 ].…”
Section: Resultssupporting
confidence: 92%
“…Therefore, it is not worth to add more cores at some point when the computation time became saturated. This is consistent with the findings by Abas and Abdul-Rahman in which it was found that as the number of cores increases for similar applied problem, at some point it will reach saturation point where most of the computation time is spent on the interconnection and communication between individual cores [ 75 ].…”
Section: Resultssupporting
confidence: 92%
“…Nadal et al [21] proposed an explicit-type recovery error estimator in the energy norm for the linear elasticity problem using smooth solution. Abbas and Abdul Rahman [22] proposed an energy norm based error estimator for a dual hp-adaptive procedure used in the numerical assessment of fluid-structure interaction. Ulku et al [23] developed a recoverytype a posteriori error estimator for gradient elasticity by revisiting basic equations of the Aifantis gradients elasticity theory.…”
Section: Introductionmentioning
confidence: 99%
“…Two main approaches can be considered in simulating the underfill flow propagation; either microscale or macroscale formulation. For the macroscale formulation, for instance finite volume method (FVM) or finite element method (FEM), the domain is discretized into volume or element that contains a collection of particles (macro scale) in which the physical properties (velocity, pressure and temperature) are represented by the nodal values [ 8 – 11 ]. Whereas in the microscale approach, the medium is assumed to be made up of particles that is continuously colliding with each other.…”
Section: Introductionmentioning
confidence: 99%